Pulmonary Varix: An Uncommon Pulmonary Vascular Anomaly. Issue 2 (March 2017) - Gleason, James B.; Shekar, Saketh Palasamudram; Hernandez, Felix; Valentin, Ramon; Mehta, Jinesh P.
Abstract : Pulmonary varices are rare lesions reflecting localized dilation of one or more pulmonary veins. These anomalies are rare, with <100 cases reported in the literature. Pulmonary varices are usually discovered incidentally and may be characterized as congenital or acquired; the latter are often related to occlusion of the distal pulmonary venous vasculature, hepatic cirrhosis, or mitral valve disorders, such as mitral stenosis or regurgitation. Pulmonary varices may not be visible on chest radiography, or may present as solitary pulmonary nodules, typically adjacent to the left atrium. Thoracic computed tomography may show tortuous, serpiginous vessels without a vascular nidus and normal-appearing pulmonary arteries, allowing varices to be distinguished from pulmonary arteriovenous malformations. Catheter pulmonary angiography may be used to diagnose pulmonary varices and exclude the possibility of arteriovenous malformations; catheter pulmonary angiography will show one or more dilated vessels leading to the left atrium opacifying on the delayed phase of contrast injection similar to other pulmonary veins, with normal-appearing pulmonary arteries. Treatment is usually unnecessary, unless the varix rapidly increases in size. Pulmonary varices are usually asymptomatic and treatment is rarely required, unless complications, such as hemoptysis, thromboembolic disease, or rupture, occur; in this case treatment is typically directed at the underlying cause for elevated left atrial pressure, although surgical resection may be considered for selected patients.